2022
DOI: 10.1108/agjsr-05-2022-0068
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of ketone with 2-methyl-1-butanol/2-ethyl-1-butanol at various temperatures

Abstract: PurposeThe paper aims to throw light on the interactions taking place between the different chemical compositions at various temperatures. P-methylacetophenone is a polar dissolvable, which is positively related by dipole–dipole co-operations and is exceptionally compelling a direct result of the shortfall of any critical primary impacts because of the absence of hydrogen bonds; hence, it might work an enormous dipole moment (μ = 3.62 D). Alcohols additionally assume a significant part in industries and resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Established literature values served as the reference point for alcohol data. Table presents a comparison between the findings of this experimental study on 2E1B and those reported in prior scientific publications. ,, An Anton Paar SVM 3000 viscometer was utilized to measure density and viscosity data by using two cylinders rotating at different speeds. The outer cylinder spins very fast, while the inner cylinder spins more slowly.…”
Section: Methodsmentioning
confidence: 99%
“…Established literature values served as the reference point for alcohol data. Table presents a comparison between the findings of this experimental study on 2E1B and those reported in prior scientific publications. ,, An Anton Paar SVM 3000 viscometer was utilized to measure density and viscosity data by using two cylinders rotating at different speeds. The outer cylinder spins very fast, while the inner cylinder spins more slowly.…”
Section: Methodsmentioning
confidence: 99%